2013
DOI: 10.1080/19425120.2013.799618
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of an Intersexual Blacktip Shark in the Northern Gulf of Mexico, with Notes on the Standardization of Classifications for This Condition in Elasmobranchs

Abstract: An intersexual Blacktip Shark Carcharhinus limbatus with a testis, immature female reproductive tracts (embedded), and claspers was caught in the Gulf of Mexico. Histology of the single gonad revealed that all stages of spermatogenesis were occurring; however, the absence of ovaries and a male duct system suggests that neither sex would have been functional in this individual. Intersexuality has been reported in 17 families and 36 species of elasmobranchs. The degree to which the different sexes are present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…As this intersexual specimen had claspers as well as gonadal tissue and tracts for both sexes, it can be classified as a complete intersexual (Hendon et al 2013). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As this intersexual specimen had claspers as well as gonadal tissue and tracts for both sexes, it can be classified as a complete intersexual (Hendon et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The histological analysis of the ovotestis revealed that the testicular tissue consisted of spermatocytes at different stages of spermiogenesis (Figure 2), including late-stage spermatids that were considered to be mature (Chen et al 1999;Lam 2009), and the ovarian portion showed maturing ova (Figure 2), which was enlarged and contained a high density of yolk granules (Teshima 1981;Lam 2009). As this intersexual specimen had claspers as well as gonadal tissue and tracts for both sexes, it can be classified as a complete intersexual (Hendon et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The externally male specimen was further dissected to verify its male sex as abnormities and hermaphroditism is also known to occur in diverse lineages of sharks (Yano & Tanaka, 1989;Iglésias et al, 2005;Ribeiro-Prado et al, 2009;Costa et al, 2013;Hendon et al, 2013). The dissection was documented at different stages using a Panasonic digital camera DMC-TZ26 (www.panasonic.com).…”
Section: Methodsmentioning
confidence: 99%